2019
DOI: 10.1136/archdischild-2019-316851
|View full text |Cite
|
Sign up to set email alerts
|

Problems of feeding, sleeping and excessive crying in infancy: a general population study

Abstract: ObjectiveTo study regulatory problems (RPs) of feeding, sleeping and excessive crying in infancy, and explore the influence of maternal mental health problems and parent–child relationship problems.Design and settingData were collected in the general child health surveillance delivered to infant families by community health nurses (CHNs). Information on CHNs’ assessments and conclusions were obtained on 2598 infants and merged with data from national registers. Descriptive statistics and logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 33 publications
2
49
3
2
Order By: Relevance
“…Confidence in the validity of associations is increased when other studies with different designs (cohort studies, community studies) and methods of recording RPs in different settings (eg, countries, health systems) produce consistent findings. First, the findings by Olsen et al 3 are consistent with previous studies that reported persistence of RPs from 5 to 6 months onwards as well as further dysregulation across childhood 4. Second, parenting is considered as a major influence on the developing infant’s behaviour regulation.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Confidence in the validity of associations is increased when other studies with different designs (cohort studies, community studies) and methods of recording RPs in different settings (eg, countries, health systems) produce consistent findings. First, the findings by Olsen et al 3 are consistent with previous studies that reported persistence of RPs from 5 to 6 months onwards as well as further dysregulation across childhood 4. Second, parenting is considered as a major influence on the developing infant’s behaviour regulation.…”
supporting
confidence: 83%
“…This persistence was found irrespective of early mental health problems or parent-child relationship problems, although these problems co-occur often with RPs. This study3 demonstrates that information on RPs and parenting can be recorded within the usual health setting by child nurses. The strength of the study is the large sample size (>2500 children) while limitations are that interobserver reliability could not be recorded and the nurses were observing and also actively intervening, possibly reducing persistence of RPs.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Despite evidence suggesting that poor sleep in infancy is associated with poorer mental health during childhood, little high-quality research has been carried out to investigate this association further. Treating infant sleep problems within the first 12 months may prevent both later sleep problems and mental health difficulties during childhood,7 but we do not know whether infant sleep problems continue to be associated with mental health past the age of 5, or whether specific psychiatric diagnoses are more prevalent for this group.…”
Section: Introductionmentioning
confidence: 99%